Mathematical model of estimation fighting losses in with provision for conditions of the exploring and management systems organization, sample of the arms, influence suddenness and entering reserve factors - Obriadin, V. V.; Antonets, V. V.; Ovcharenko, V. V. (Honor and Law, 2019)
The Considered questions of the creation and use to mathematical model of the estimation of the mutual losses intermix armed subdivisions in fighting, which can appear in local conflict. The Model provides undertaking the analysis interference in process boa factor, which characterize activity of the created system of the exploring, degree of the improvement managerial system by fire, influence of the factor to surprises in opening of the fire and determination of time of the entering reserve.